Mathematical correlation for the strain signal energy characteristics obtained from instrumented charpy impact test - Ali, Mohd Basri; Abdullah, Shahrum (Pensee Journal, 2014)
This paper presents the correlation analysis of the energy obtained from impact strain signals with absorbed energy then develops a mathematical expression. The total absorbed energy obtained using the dial system may be significantly different, depending on the strength of material and ductility of test specimen. Little research has been performed in develop mathematic expression, but it is important for evaluating impact signals because as an input signals in finite element analysis (FEA) impact tests and for obtaining additional information on material deformation and fracture processes under impact loading. In this experiment, strain gauges were connected between the charpy impact striker and the high frequency data acquisition system in order to capture the dynamic impact strain response. Aluminium alloy of 6061-T6 specimens with different velocities and thicknesses were used, which they were designed according to the ASTM E23. For the analysis an obtained signal was converted from the time domain to the frequency domain by means of the power spectrum density (PSD) method and the area under its plot was used to calculate strain energy. The comparison between energy absorbed with the strain energy was performed, and regression method based on the equation for vibration response under a non-periodic force was used to evaluate the charpy impact signals. The correlation between the strain energy from PSD and the absorbed energy can be linked by a polynomial equation with 99.8% correlation, where the PSD energy influences or related to the absorbed energy. The equations developed using the regression approach showed the correlation or R2 values greater than 97.7%, showing an accuracy of the closeness in the data. This energy correlation can be used as an alternative and the constructed equations were determined to be suitable for evaluating charpy impact strain signal patterns. Finally the evaluation process of impact strain signal can be proposed.